The politics of hero myth in President Jokowi's biopic film (2013) - Muhammad Dzaky Abdullah; Ari J. Adipurwawidjana; Muhamad Adji (Universitas Muhammadiyah Malang, 2025)
Among the prominent Indonesian biographical films concerning